Fractures in children with cerebral palsy: a total population study. (11th June 2013) - Uddenfeldt Wort, Ulrika; Nordmark, Eva; Wagner, Philippe; Düppe, Henrik; Westbom, Lena
Abstract : Aim: To analyse factors associated with fractures in children with cerebral palsy (CP) in different levels of Gross Motor Function Classification System (GMFCS). Method: This was an epidemiological retrospective study of a total population of 536 children (214 females, 322 males) with CP born between 1990 and 2005. CP type was unilateral spastic ( n =159), bilateral spastic ( n =225), ataxic ( n =60), dyskinetic ( n =80), and mixed type ( n =12); 384 children were in Gross Motor Function Classification Scale (GMFCS) levels I–III and 152 children were in GMFCS levels IV–V. Data were collected for a 9‐year period on sex, CP‐type, GMFCS level, gastrostomy, height, weight, the use of a standing device, antiepileptic drug (AED) therapy, and fractures. Results: The risk of fracture in the total population of children with CP was similar to that for typically developing children. The risk for fractures of those in GMFCS levels I–III was not significantly associated with any of the studied risk factors. The risk of fractures for those in GMFCS levels IV–V on AED therapy was a twofold increase ( p =0.004). The risk for fractures without trauma in children with stunted growth (height for age <−3 SD) and those who did not use standing devices was significantly increased: adjusted incidence rate ratio (AIRR) 4.16 ( p =0.011) and 3.66 ( p =0.010) respectively. Results regarding gastrostomy feeding for those in GMFCS levels IV–V were conflicting: a gastrostomy was associated with a reduced risk of fractures with trauma, but with increased risk of fractures without trauma (AIRR 0.10, p =0.003 and 4.36, p =0.012) respectively. Interpretation: Children in GMFCS levels I–III had a similar incidence and pattern for fractures as normally developing children. Those in GMFCS levels IV–V had stunted growth, often a sign of longstanding undernourishment, and were associated with an increased risk of fractures. Children using standing devices had a fourfold reduction of fractures without trauma. Regular loading exercises and early adequate nutritional intake could prevent fractures in severe CP. Abstract : This article is commented on by Henderson on pages779–780 of this issue.